Emulsion and microstructure design for controlled digestion - Liu, Wentao (2018)
There has been growing interest in research focused on understanding the breakdown properties of foods in the gastro-intestinal (GI) tract, with a view to better design food systems that can control digestion with additional beneficial physiological effects (e.g satiety) to help tackle the obesity epidemic. The objective of the work presented in this thesis was to design a novel food emulsion microstructure, based on a dairy food matrix, to control digestion (measured in vitro). To achieve this, initially, skimmed milk powder (SMP), and either low or high molecular weight guar gum (GG) were used to establish SMP-GG phase diagrams at 5oC and pH 6.5 to better understand the phase behaviours of these systems. As expected, the compatibility of the SMP-GG system was found to increase with decrease in molecular weight of the GG. Confocal laser scanning microscopy (CLSM) clearly showed that the microstructure was dependent upon starting composition which in turn determined the relative phase volume of the two phases. This phase separated microstructure of SMP-GG can be considered as a water-in- water (W/W) emulsion. Through the incorporation of oil into these systems with designed microstructures based on the phase diagram, it was possible to form model systems of SMP-GG-OIL, showing the lipid phase within the protein phase within the polysaccharide phase. This can be described as ‘Matryoshka Composites’ and therefore being viewed as ‘O/W/W’ emulsion when the starting aqueous phase is either polysaccharide continuous or bi-continuous. Although the addition of a low volume fraction of oil has indicated an influence on the thermodynamic equilibrium of the SMP-GG system, through chemical analysis and rheological measurement; the in vitro digestibility of such phase separated model systems of SMP-GG-OIL with different microstructures was investigated using a pH Stat method. The microstructures were shown to be able to control lipid digestion. For a selected tie-line, the lipolysis of protein continuous > bi-continuous > polysaccharide continuous system, at a certain level of oil addition. The mechanism involved in the lipolysis of the designed formulations/microstructures was dependent upon the protein, rather than GG, and was driven by the protein concentration. As a comparison, in the case of adding different amounts of oil, the lipolysis was found to decrease with increasing oil phase volume. Confocal laser scanning microscopy revealed structural changes that occurred to the emulsified lipid droplets as they passed through a model gastro-intestinal (GI). The effect of the addition of non-ionic surfactants (Tween 20) on lipolysis of 20% sunflower oil included in the SMP-GG system has also been studied via the pH Stat method, as commercial products often contain other surface active materials. The presence of Tween 20 increased lipolysis, although it resulted in the increased droplet size arising from emulsion destabilization due to the competitive adsorption of protein and Tween 20 at the O/W interface leading to depletion flocculation. Moreover, the ‘unexpected synergism’ between Tween 20 and protein in facilitating lipolysis was enhanced with increasing Tween 20 concentration, indicating partial displacement of proteins by Tween 20 at the interface. The droplet surface laden with both protein and Tween 20 appeared like the surface of a ‘Golf Ball’ surface, so a 3D ‘Golf Ball’-like interfacial displacement model has been proposed. In contrast, if complete displacement occurred, lipolysis in the presence of Tween 20 was not further increased nor was it decreased. In addition, the oil type and physical state of lipid demonstrated an influence on lipolysis, but this was mainly dependent upon the lipid compositions and their melting points. These findings suggest the potential applications for food product design in regulating satiety effects by triggering the Ileal brake mechanism, and may provide opportunities to control delivery of specific nutrients during digestion.